Rethinking social studies and history education : social education through alternative texts - White, Cameron (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
The book is unique in that it mixes theory and practical applications in rethinking traditional social studies education. It focuses on essays integrating media, popular culture, and alternative texts for teaching and learning in social studies and history education through a social education lens. Social education integrates social studies, media / popular culture, and cultural studies all within a social justice framework.The text provides 20+ curriculum themes with strategies to connect in teaching and learning, along with resources to extend depth of understanding. In addition, the pedagogical philosophy inherent in the essays is student-centered learning focusing on issues, problem, and project-based instruction. Although the themes are generally social studies and history focused, the links to media and popular culture can be integrated in other disciplines.